مساهمة التدقيق الداخلي في دعم حوكمة الشركات دراسة ميدانية - اسراء مدلل; هاجر محمودي; هدى هاني; صفية نصري (جامعة الوادي university of eloued, 2024)
تناول الدراسة أهمية التدقيق الداخلي في دعم حوكمة الشركات، وقد تـــــم الاعتمـــــاد على الفلسفة الوضعية Pisivitism القائمة على المقاربة Deductive ، حيث تم تصميم استبيان وتوزيعه على عينة من37فرد والمتمثلة في إطارات في العديد من المؤسسات والأساتذة الباحثين ومحافظي وخبراء المحاسبة، اعتمدنا في تحليله على برنامج Spss وتوصلت الدراسة إلى عدة نتائج منها مساهمة التدقيق الداخلي في دعم حوكمة الشركات، من خلال دوره في تقييم نظام الرقابة الداخلية والمساعدة في إدارة المخاطر وعلاقته التعاونية مع مجلس الإدارة ولجنة التدقيق. This study explores the significance of internal auditing in the establishment of corporate governance. The research relies on the positivist philosophy and employs a deductive approach. We designed and distributed a questionnaire to a sample of 37 individuals, which included executives from various institutions, academic researchers, accountants, and accounting experts. The analysis was conducted using SPSS software. The study reached several conclusions, including the contribution of internal auditing to establishing corporate governance through its role in evaluating the internal control system, assisting in risk management, and its collaborative relationship with the board of directors and the audit committee.
مذكرة ماستر
Keywords: التدقيـــق الداخلي،حوكمة الشركات، الرقابة الداخلية، إدارة المخاطر، مجلس الإدارة، لجنة التدقيق. internal auditing; corporate governance; internal control; risk management; board of directors; audit committee.